Electronic structure of PCBM - 盛春荠 王鹏 沈影 李艳君 张文华 徐法强 朱俊发 来国桥 李宏年 (Chinese physics B, 2012)
We have studied the electronic structure of [6,6]-phenyl-C61-butyric-acid-methyl-ester （PCBM） using synchrotron radiation photoelectron spectroscopy （PES） measurements and first-principles calculations. The PES spectrum of the entire occupied valence band is reported, which exhibits abundant spectral features from the Fermi level to - 24 eV binding energy. All the spectral features are broadened as compared with the cases of C60. The reasons for the broadening are analysed by comparing the experimental data with the calculated energy levels and density of states. Special attention is paid to the analysis of the C60 highest occupied molecular orbitM （HOMO）-1 derived states, which can play a crucial role in the bonding at the interfaces of PCBM/polymer blenders or PCBM/electrodes. Besides the well-known energy level splitting of the C60 backbone caused by the lowered symmetry, C 2p states from the side chain mix or hybridize with the molecular orbitals of parent C60. The contribution of the O 2p states can substantially modify the PES spectrum.